Motherhood: an impediment to workplace progression? The case of Cyprus. Issue 5 (20th June 2016) - Socratous, Maria; Galloway, Laura; Kamenou-Aigbekaen, Nicolina
Abstract : Purpose: The purpose of this paper is to identify potential explanations on why motherhood affects the non-progression of women, in Cyprus, to the top of the organisational ladder. Design/methodology/approach: For the purposes of the study a qualitative approach was taken and semi-structured interviews were used. The interviews were conducted with specific, preselected employment groups. These were chartered accountants from the Big Four (PWC, Deloitte, Ernst & Young, KPMG) companies in Cyprus and academics working at the University of Cyprus. Findings: It has been identified through the interviews that women in Cyprus are faced with impediments on their way to the upper levels of the organisational ladder. The reasons for this vary and one of the most important is the motherhood effect. In particular, the research suggests that cultural norms and perceptions that women should be the primary caregiver are a barrier to advancement for women and there is a lack of family friendly policies and childcare facilities at least in the organisations included in this study. Originality/value: This paper sheds light into a previously under-researched area; gender equality in Cyprus. The author also denotes the problems a mother is faced with on her way to the top of the organisational ladder and that culture is of utmost importance with regards to the role of women in the society and the workplace in Cyprus and elsewhere.